Lightweight migration for web applications with framework separation1. (19th September 2017) - Kwon, Jin‐woo; Jeong, InChang; Moon, Soo‐Mook
Summary: Web applications (apps) are programs created by web technologies such as HTML, CSS, and JavaScript. Web apps can be executed on any platform that supports a web browser. Such portability allows an interesting user experience called app migration, which can save an app's execution state to a file called snapshot, transmit it to another device, and continue the execution using the snapshot. However, existing approaches save all the states of the current app, regardless of its relevance to an app's state, making the snapshot size and snapshot creation time infeasibly large. For example, web apps are often programmed using web frameworks such as jQuery, which are libraries written in JavaScript to support app developments. We found that most objects created by frameworks during their initialization are not relevant to an app's state. Hence, one idea to reduce the snapshot size is not saving those framework objects in the snapshot but creating them after migration via re‐initialization. Unfortunately, this is not always straightforward since the framework objects are intermingled with the app objects in the heap, possibly pointing to each other. To resolve this, we separated app objects that are attached to framework objects by monitoring app's execution and saved them to the snapshot. This paper proposes such a framework separated migration technique, with optimization to reduce the overhead, especially related to monitoring app's execution. With our approach, we could reduce the snapshot size by 89.1% on average and shorten the migration time by 47.6%, increasing the feasibility of app migration.